"Waste to Wealth": Lignin as a Renewable Building Block for Energy Harvesting/Storage and Environmental Remediation. Issue 11 (30th April 2020) - Wang, Ding; Lee, Sahng Ha; Kim, Jinhyun; Park, Chan Beum
Abstract: Lignin is the second most earth‐abundant biopolymer having aromatic unit structures, but it has received less attention than other natural biomaterials. Recent advances in the development of lignin‐based materials, such as mesoporous carbon, flexible thin films, and fiber matrix, have found their way into applications to photovoltaic devices, energy‐storage systems, mechanical energy harvesters, and catalytic components. In this Review, we summarize and suggest another dimension of lignin valorization as a building block for the synthesis of functional materials in the fields of energy and environmental applications. We cover lignin‐based materials in the photovoltaic and artificial photosynthesis for solar energy conversion applications. The most recent technological evolution in lignin‐based triboelectric nanogenerators is summarized from its fundamental properties to practical implementations. Lignin‐derived catalysts for solar‐to‐heat conversion and oxygen reduction are discussed. For energy‐storage applications, we describe the utilization of lignin‐based materials in lithium‐ion rechargeable batteries and supercapacitors (e.g., electrodes, binders, and separators). We also summarize the use of lignin‐based materials as heavy‐metal adsorbents for environmental remediation. This Review paves the way to future potentials and opportunities of lignin as a renewable material for energy and environmental applications. Abstract : Waste to Wealth : Lignin is the second most earth‐abundant organic material that exhibits various attractive physicochemical properties; however, it has been underutilized due to its recalcitrant nature. This Review introduces recent developments in lignin processing, integration, and applications in the areas of energy conversion, energy storage, and environmental remediation.